The Process of Estalbishing a Shared Service Center with the Example of Euroflorist - Hauke-Lopes, Aleksandra (Studia Oeconomica Posnaniensia, 2026)
The paper presents the process of creating and initial management of the Euroflorist Shared Services Center in Poznań. As the result of the strategic approach to managing the migration processes, the company has succeeded in achieving its goals in the scheduled time. This paper describes the stages of preparation to the migration, the transfer processes and the actions that have been undertaken by the managers to gain the knowledge necessary to execute the processes at the Shared Services Center in Poznań. Due to the systematic approach to the data migration and the management of establishing the Shared Service Center, the process is considered as being successful.